Predictors of practices related to dengue fever prevention among international students in Universiti Putra Malaysia, Serdang - Rao, G.; Minhat, Halimatus Sakdiah; Kadir @ Shahar, Hayati (Community Health Society Malaysia, 2016)
Background: Dengue fever is a vector-borne, notifiable and preventable communicable disease. This study aim to determine the practices and the contributing factors related to dengue fever prevention among the international students in Universiti Putra Malaysia, Serdang. Materials and Methods: A cross sectional study was conducted using cluster sampling proportionate to size. Data were collected using a validated, self-administered questionnaire which consist of six sections namely socio-demographics factors, knowledge, attitude, influence of mass media, previous history of dengue fever and practices related to dengue fever prevention. Data was analyzed using IBM Statistical Package for Social Science (SPSS) version 21.0 comprising descriptive, bivariate and multivariate analysis and level of significance was set P<0.05. Result: A total of 641 respondents were involved with the response rate of 95.7%. The mean age of the respondents was 33.41±6.56 years old. Majority of the respondents were Asian (74.6%), male (65.5%), married (61.5%), had poor knowledge (45.9%), showed negative attitude (51.6%) and demonstrated good practices related to dengue fever prevention practices (53.7%). The significant predictor for poor practices were negative attitude towards practice (aOR=3.705, 95%CI=2.532–5.421, P<0.001), low influence of mass media towards practice (aOR=0.274, 95%CI=0.188–0.399, P<0.001), poor knowledge (aOR=0.169, 95%CI=0.090–0.319, P<0.001) and moderate knowledge on dengue fever (aOR=0.439, 95%CI=0.234–0.825, P<0.010). Conclusion: The findings revealed good practices among the respondents despite their poor knowledge and negative attitude towards dengue fever. Therefore knowledge based health education and cultivating positive attitude should be further reinforced to strengthen the dengue fever preventive practice.